Recent progress in the mechanisms, preparations and applications of polymeric antifogging coatings - Gong, Xiaodan; Yu, Haojie; Wang, Li; Liu, Xiaowei; Ren, Shuning; Huang, Yudi; Huang, Zhikun (Advances in colloid and interface science, 2022)
Fog on a solid surface is prejudicial to its optical properties and will even cause hygienic and safety concerns in some exceptional cases. Thus, antifogging coatings have attracted great interest in fundamental research and industry applications. Superhydrophilic and superhydrophobic coatings have been mainly explored and described in the antifogging field. In recent years, hygroscopic antifogging coatings of hydrophilic and hydrophobic parties have been introduced due to their unique properties. In this review, three antifogging mechanisms are reviewed to provide design strategies for antifogging surfaces. The current techniques for fabricating polymeric antifogging coatings are discussed in depth. The recent progress in materials and structures for antifogging surfaces is briefly summarize. Finally, the practical applications and outlooks related to multifunctional antifogging coatings are mentioned.Fog on a solid surface is prejudicial to its optical properties and will even cause hygienic and safety concerns in some exceptional cases. Thus, antifogging coatings have attracted great interest in fundamental research and industry applications. Superhydrophilic and superhydrophobic coatings have been mainly explored and described in the antifogging field. In recent years, hygroscopic antifogging coatings of hydrophilic and hydrophobic parties have been introduced due to their unique properties. In this review, three antifogging mechanisms are reviewed to provide design strategies for antifogging surfaces. The current techniques for fabricating polymeric antifogging coatings are discussed in depth. The recent progress in materials and structures for antifogging surfaces is briefly summarize. Finally, the practical applications and outlooks related to multifunctional antifogging coatings are mentioned.